ANALISIS MOTIVASI KERJA TERHADAP KINERJAKARYAWAN PADA CARREFOUR KAREBOSI LINK DI KOTA MAKASSAR - Fitrianti, A Nur; Alimuddin, Chaerani (Perpustakaan dan Penerbitan Unismuh Makassar, 2016)
This research is a quantitative research using interview and survey approach. The purpose of this study is to determine the effect of Work Motivation Employee Performance On Carrefour Karebosi Linkdi Makassar. By using saturated sample sebanyank 58 respondents. Methods of data collection using questionnaires with likert scale. Data processing is done by using simple regression analysis.The findings of this study can be concluded that there is a significant relationship between employee motivation on employee performance at Carrefour Karebosi Link in Makassar. In the research above thesis that has been done there is a simple regression analysis results that have a value of 0.68 and T test conducted states that Ho is rejected and accept Ha.